Preliminary findings of alternative dispute resolution (ADR) application by the G7 contractors in the Malaysian construction industry - Ismail, Zulhabri; Abdullah, Jamalunlaili; Mohamad Zin, Rosli (2008)

(untitled)
The research described in this paper investigates the application of Alternative Dispute Resolution (ADR) by the Malaysian CIDB G7 registered construction contractors. The objective of the research is to analyse the application of ADR in the Malaysian construction industry in term of quantity, trend and obstacles. This research adopted quantitative methodology based on cross sectional survey instrument to 1000 contractors from the available sampling frame consists of 2,834 building and civil engineering contractors nationwide and the response rate was 231 (23%) which is acceptable rate for social science research. The data collected has been analysed using descriptive analysis and nonparametric statistics using SPSS 15. It was found that currently ADR is not very applicable in the Malaysian construction industry. At the same time the application of ADR is not strongly influenced by the years of establishment of the construction organisations, experience and designation of respondents, value of contract price and project duration. Overall, the level of application of ADR by the G7 construction contractors are generally low due to the characteristics, perceptions and understanding on the overall process of dispute resolution. These preliminary research findings will form a basis for the establishment of a construction ADR framework for practical utilisation in the Malaysian construction industry.